Management factors related to calf morbidity and mortality rates - PEREZ, E. (1990)
An observational epidemiological study was carried out on 63 commercial Dutch dairy farms. The relationship between managerial procedures and morbidity and mortality patterns in 1037 dairy calves from birth to 4 months of age was investigated. Data on health disorders concerned dullness at birth, diarrhoea, navel disorder and respiratory disease. Relationships were quantified by relative risk estimation and trends were studied by using life tables for age groups and calendar months. Descriptive results largely reflect common management procedures and are comparable with other reported data. Several managerial factors were shown to have a significant influence, either increasing or decreasing, on the risk of occurrence of diarrhoea, respiratory disease and mortality. The impact of other variables remains uncertain, pointing to the need for further studies. The application of epidemiological methods could be a powerful tool to quantify the risk associations between disease state and animal, herd, management or environmental factors. Veterinary-zootechnical programmes for herd health and production control could be further improved in that way.